Preliminary Safety and Potential Effect of 6B11-OCIK Adoptive Cell Therapy Against Platinum-Resistant Recurrent or Refractory Ovarian Cancer - Cheng, Hongyan; Ma, Ruiqiong; Wang, Shang; Wang, Yu; Li, Yingchun; Tang, Zhijian; Dou, Sha; Wang, Yuanfen; Zhu, Honglan; Ye, Xue; Zhang, Tianyu; Zhang, Yonghua; et al. (Frontiers in Immunology, 2021)
Ovarian cancer is a leading cause of death among gynecological malignancies, and novel therapies are urgently needed. Here we report preliminary findings on the potential safety and efficacy of 6B11-OCIK, an adoptive cell therapy of autologous T cells induced by the humanized anti-idiotypic antibody 6B11 minibody plus dendritic cells and cytokines, against platinum-resistant recurrent or refractory ovarian cancer in three patients. We found that 6B11-OCIK treatment was safe and well tolerated after five cycles of intravenous infusion with an initial dose of 1–2×109 cells and a dose-climbing strategy. Hemoglobin, platelets, white cell count, creatinine or liver enzyme values, coagulation function, kidney and heart function were not significantly affected over the duration of therapy. Two of the three enrolled patients showed potentially drug-related grade 1 and 2 weakness, and no other adverse events were observed. Of the three enrolled patients, one had stable disease and two showed disease progression. The patient with favorable clinical efficacy had better immune response as measured by 6B11-OCIK proliferation capacity, activation ability of CD3+CD8+ tumor-specific cytotoxic T lymphocytes and CD3+CD56+ cytokine-induced killer cells, and tumor cell killing efficiency. Changes in circulating tumor cells after treatment were consistent with serum level CA125 in the patient with stable disease (both decreased), while differences were observed in the two patients with disease progression (increased CA125 in both and decreased CTC in the patient with better immune response), suggesting that variation of circulating tumor cells was more consistent with immune response and reflected efficacy directly. This preliminary study suggested that autologous 6B11-OCIK treatment was safe and had potential clinical efficacy against ovarian cancer. Patients with better immune response had more favorable efficacy. In addition to imaging, CA125 and immunophenotypes, CTC monitoring may represent a potential indicator of immunotherapy response.